Assessment of Bacterial Contamination in Locally Manufactured Cheese from Selected Factories in Tripoli City - Samira Jarad (AlQalam Journal of Medical and Applied Sciences, 2024)
It is now a new tomorrow in the food industry, where food materials are available, but can be exposed to threats from microbial contamination that may affect its quality and safety. This study aimed to evaluate bacterial contamination in local honey from four different factories in Tripoli, Libya. Twelve samples of cheese were collected, three samples from each factory, and were analyzed for microbial contamination. The results showed microbial contamination of the cheese, as the production of the first factory and the third factory had a large bacterial record, especially with Proteus spp. and Staphylococcus aureus Two types of bacteria cause food poisoning.,. In contrast, the second factory showed new production, while the fourth factory showed the presence of bacteria in low levels. These results indicate the importance of adhering to good hygiene practices, pasteurization protocols, and optimal storage conditions in cheese making and food safety. The study also highlights the ongoing need for quality control in monitoring and preventing microbial spoilage. In addition, the standard study emphasizes the importance of Libya Specification 354 of 1992 regarding microbial limits in cheese making and consumer safety. لقد أصبح الغد جديداً في صناعة الأغذية حيث تتوفر المواد الغذائية ولكنها قد تتعرض لتهديدات التلوث الميكروبي الذي قد يؤثر على جودتها وسلامتها. هدفت هذه الدراسة إلى تقييم التلوث البكتيري في العسل المحلي من أربعة مصانع مختلفة في طرابلس ليبيا. تم جمع اثنتي عشرة عينة من الجبن، ثلاث عينات من كل مصنع، وتم تحليلها للتلوث الميكروبي. أظهرت النتائج تلوث الجبن بالميكروبات، حيث كان إنتاج المصنع الأول والمصنع الثالث سجلاً بكتيريًا كبيرًا، خاصة بـ Proteus spp. و Staphylococcus aureus، وهما نوعان من البكتيريا تسبب التسمم الغذائي. في المقابل، أظهر المصنع الثاني إنتاجًا جديدًا، بينما أظهر المصنع الرابع وجود البكتيريا بمستويات منخفضة. تشير هذه النتائج إلى أهمية الالتزام بممارسات النظافة الجيدة وبروتوكولات البسترة وظروف التخزين المثلى في صناعة الجبن وسلامة الغذاء. كما تسلط الدراسة الضوء على الحاجة المستمرة لمراقبة الجودة في مراقبة ومنع التلف الميكروبي. بالإضافة إلى ذلك، تؤكد الدراسة القياسية على أهمية المواصفة الليبية 354 لسنة 1992 بشأن الحدود الميكروبية في صناعة الجبن وسلامة المستهلك